Experimental determination of hydrogen isotope exchange rates between methane and water under hydrothermal conditions. (15th July 2022) - Turner, Andrew C.; Pester, Nicholas J.; Bill, Markus; Conrad, Mark E.; Knauss, Kevin G.; Stolper, Daniel A.
Abstract: The hydrogen isotopic composition of methane (CH4 ) is used as a fingerprint of gas origins. Exchange of hydrogen isotopes between CH4 and liquid water has been proposed to occur in both low- and high-temperature settings. However, despite environmental evidence for hydrogen isotope exchange between CH4 and liquid water, there are few experimental constraints on the kinetics of this process. We present results from hydrothermal experiments conducted to constrain the kinetics of hydrogen isotope exchange between CH4 and supercritical water. Seven isothermal experiments were performed over a temperature range of 376–420 °C in which deuterium-enriched water and CH4 were reacted in flexible gold reaction cell systems. Rates of exchange were determined by measuring the change in the δD of CH4 over the time course of an experiment. Regression of derived second order rate constants (kr ) vs. 1000/T (i.e., an Arrhenius plot) yields the following equation: ln(kr ) = −17.32 (±4.08, 1 s.e.) × 1000/T + 3.19 (±6.01, 1 s.e.) (units of kr of sec −1 [mol/L] −1 ), equivalent to an activation energy of 144.0 ± 33.9 kJ/mol (1 s.e.). These results indicate that without catalysts, CH4 will not exchange hydrogen isotopes with liquid water on a timescale shorter than the age of the Earth (i.e., billions of years) at temperatures below 100–125 °C. Exchange at or below these temperatures is thought to occur due to the activity of life, and thus hydrogen isotopic equilibrium between methane and water may be a biosignature at low temperatures on Earth (in the present or the past) and on other planetary bodies. At temperatures ranging from 125 to 200 °C, hydrogen isotope exchange between CH4 and liquid water can occur on timescales of millions to hundreds of thousands of years, indicating that in thermogenic natural gas systems CH4 may isotopically equilibrate with water and achieve equilibrium isotopic compositions. Finally, the kinetics indicate that in deep-sea hydrothermal systems, the hydrogen (and thus clumped) isotopic composition of CH4 is likely set by formation and/or storage conditions isolated from the active flow regime. The determined kinetics indicate that once methane is entrained in circulating fluids, the expected time-temperature pathways are insufficient for measurable hydrogen isotope exchange between CH4 and water to occur.